Equilíbrio térmico e emissão de metano em vacas Jersey - Carvalho, Marcos Davi de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present work aimed to study the physiological variables and enteric methane emission in Jersey breed dairy cow, relating with environmental variables. To understand the dynamics of thermal equilibrium was conducted an experiment where we used twelve animals of Jersey breed lactating cow with average daily production of 17.7 L/day, by the herd of APTA of Ribeirão Preto, the average of 362.3 ± 31.0, not pregnant and with an average of two months of lactation. An experiment was conducted adopting an experimental Latin square design where 12 animals were evaluated during 12 days of data collection and being observed for 12 hours long. The skin surface temperature was strongly correlated with the environmental meteorological variables (temperature and relative humidity), and its coefficient of correlation was equal to 0.69, -0.50 and weakly correlated to the solar radiation -0.11. The lowest average of rectal temperature was 38.5 ± 0.33 ° C and the highest was 40.3 ± 0.05 ° C. The coat surface temperature increased until around 16:00 hours, and after that it began to decrease, while the epidermis had a decrease starting from 18:00 hours. The temperature of the epidermis showed a positive correlation with the hair coat temperature of 0.83 and with the rectal temperature of 0.55.The respiratory frequency showed a positive correlation with the air temperature, 0.35. The heat loss by respiratory evaporation showed a positive correlation with the air temperature, 0.71. So that, the high average, was at 13 hours 30.4±0.33, W m-2 and the low, around at 8 hours, with average of 12.6 ± 0.29 W m-2 while their correlation with relative humidity was -0,51. The hour and day effects was significant (P <0.01) for metabolic heat production and enteric methane emission. The correlation among methane emission and metabolic heat production was of 0.23. The analysis of variance showed that collet day, hour of class and animal were significant ...

O presente trabalho objetivou o estudo de variáveis fisiológicas e a emissão de metano entérico em bovinos de leite da raça Jersey, relacionando com as variáveis ambientais. Para entender essa dinâmica do equilíbrio térmico foi conduzido um experimento onde foram utilizados doze animais da raça Jersey lactantes com produção média diária de 17,7 L/dia, pertencentes ao rebanho da APTA de Ribeirão Preto, o médio de 362,3±31,0, não prenhes e com média de dois meses de lactação. O arranjo experimental adotado foi em quadrado latino sendo avaliados 12 animais durante 12 dias de coleta e observados durante 12 horas. A temperatura superfície da epiderme foi fortemente correlacionada com as variáveis meteorológicas do ambiente (temperatura e umidade relativa do ar), sendo seu coeficiente de correlação igual a 0,69, -0,50 e fracamente correlacionada com a radiação -0,11. A temperatura retal apresentou a menor média diária de 38,5±0,33 °C e a maior média de 40,3±0,05 °C. A temperatura da superfície do pelame aumentou até por volta das 16:00 horas, sendo que após esse horário passou a ocorrer um decréscimo, enquanto a da epiderme tem um decréscimo a partir das 18:00 horas. A temperatura da epiderme apresentou uma correlação positiva de 0,83 com a temperatura do pelame e com a temperatura retal de 0,55. A frequência respiratória apresentou uma correlação positiva com a temperatura do ar, 0,35. A perda de calor via evaporação respiratória apresentou uma correlação positiva com a temperatura do ar, 0,71. De forma que, a maior média, às 13:00 horas, 30,4±0,33, W m-2 e a menor, em torno das 8:00 horas, com média de 12,6±0,29 W m-2 enquanto sua correlação com a umidade relativa foi -0,51. O efeito da hora do dia foi significativo (P < 0,01) para produção de calor metabólico e emissão de CH4 entérico. A correlação entre a emissão de CH4 e a produção de calor metabólico foi de 0,23. A análise...
Keywords: Bovino de leite; Vaca; Metano; Temperatura corporal - Regulação; Bovino - Metabolismo; Methane